Report on National Coordinated Evaluation of Five Models for Language Arts Reading Centers - Katzenmeyer, William G.; National Council of Teachers of English, Urbana, IL.; Specialized Educational Consultant Services, Inc., Durham, NC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Reported in this document are the evaluation results of five model teacher inservice language arts/reading projects geographically dispersed and operationally unique. Contents include an introduction describing the joint efforts of the Bureau of Educational Personnel Development and the National Council of Teachers of English in carrying out the projects, "Design and Evaluation Strategy,""Report on Site Visits,""Summary of Project Directors' Report,""Results of Teacher Practices and Attitude Survey,""Results of Study of Pupil Test Performance," and "Summary and Conclusions." Concluding the document are several appendixes on the evaluation design, data forms, and performance results obtained from the projects (Project DELTA--University of California at Berkeley and Berkeley Public Schools; Inservice Program in Reading/Language Arts--Ohio State University and Columbus Public Schools; Project PIRLT--Temple University and Philadelphia Schools; Seawell Elementary School--University of North Carolina and Learning Institute of North Carolina; and Portland State University and Portland City Schools, Oregon). (RB)
Sponsoring Agency: Bureau of Educational Personnel Development (DHEW/OE), Washington, DC.
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Research; Elementary Education; Evaluation Methods; Inservice Teacher Education; Language Arts; Models; Reading; Teacher Attitudes; Teaching Methods; Reports, Research